Caught on the surface: Tustin on autistic experience - Taipale, Joona (Frontiers in Psychology, 2023)
According to Frances Tustin, the core of autism is found in sensory modifications – and tactile modifications in particular. Tustin argues that sensory experiences may become self-absorbed to such an extent that the sensory environment experientially flattens into a two-dimensional ‘feel’, which complicates the individual’s relations with the external environment and other people. Focusing on these fundamental modifications and their experiential consequences, the article introduces Tustin’s main insight in terms of collapse of intentional depth, suggesting that this collapse concerns not only concrete spatial depth, but symbolic and intersubjective depth as well. By so doing, the article illustrates how Tustin’s ideas render intelligible certain commonly recognized features of autism, such as ”deficits in the ability to initiate and to sustain reciprocal social interaction and social communication” and “restricted, repetitive, and inflexible patterns of behaviour, interests or activities” (ICD-11).